Human trafficking in Malaysia - Ab Hamid, Zuraini (IIUM Press, International Islamic University Malaysia, 2018)
Human trafficking is a transnational organised crime which has threatened all regions around the world including Malaysia. Currently there are no books in the market that addresses the prevalent occurrence of human trafficking in Malaysia. Most of the materials such as articles, journals, books and writings are from the international market, written by foreign researchers and can only be gathered from the internet. Nevertheless, these works are very much constrained within the laws and practice in the selected countries which in certain cases are not suitable to be adopted elsewhere, especially in Malaysia due to differences in culture, geography, laws or policies. None of the writers managed to disclose the extent of human trafficking issues in a state government. Their argument also lacks concrete evidence, including absence of reliable data and statistics. Therefore, this book will be the main reference for the human trafficking issues, particularly in Malaysia since it will be among the main references published in Malaysia. The book examines all forms of human trafficking globally and revealing Malaysia’s issues on the heinous crime. It will further enhance the reader’s understanding on current phenomena of human trafficking in Malaysia, and suggesting mechanisms for the prevention of the crime, protection of the victim and prosecution of the perpetrator. The book will further provide relevant proposals to strengthen the enforcement bodies and prosecution, best approach to protect the victim and ways to enhance cooperation among the stakeholders. References are made to Australia and other countries especially on their laws and enforcement side. In addition, it will enhance the academia world where the lecturers and students will have a reference on the issue of human trafficking.